Herbicolin A, an antifungal lipopeptide produced by Pantoea agglomerans APC 4211 is a promising biocontrol agent against food spoilage fungi - Eleni Kamilari; Paula M. O'Connor; Jerry Reen; Promi Das; Aiswariya Deliephan; Daragh Hill; Oxana Fursenko; Jonathan Weise; Ay Sha Naomi Moore; Colin Hill; Catherine Stanton; Paul R. Ross (International Journal of Food Microbiology, 2026)

An experimental approach to assess the combined effects of multiple stressors on a large vertebrate species - Enrico Pirotta; Catriona M. Harris; Lori H. Schwacke; Len Thomas; Jason B. Allen; Aaron A. Barleycorn; Marco Casoli; Jonathan Crossman; Laura Aichinger Dias; Laura Engleby; Erin LaBrecque; Jenny A. Litz; et al. (Conservation Biology, 2026)
The design of experiments to investigate the combined effects of multiple stressors requires exposing target organisms to multiple combinations of stressor doses. Concurrent manipulation of stressors is often infeasible with wildlife, but long‐lasting health effects allow individual health to be used as an integrator of prior stressor exposure. The population of bottlenose dolphins in Barataria Bay, Louisiana, experienced long‐lasting health effects after exposure to oil from the Deepwater Horizon spill. We investigated whether compromised health status affects dolphins’ ability to respond to other stressors, specifically vessel traffic, potentially leading to increased collision risk. We used this case study to develop a hypothesis‐driven experimental approach to assess the combined effects of multiple stressors in a large, long‐lived vertebrate species. We conducted controlled vessel approaches to test whether the health status of targeted dolphins affected their behavioral responses. Our results highlighted some effects of health, suggesting that oil spills may exacerbate the effects of other stressors in coastal populations. For example, lung disease was associated with a delayed dive response, which could affect the ability to vertically avoid vessels and lead to increased collision risk. However, health effects on response probability were overall smaller than anticipated, and other contextual variables (e.g., sex, age, calf presence, prior experience, and exposure context) contributed to response variability. Our work demonstrated the value of formalizing stressor interactions as multidimensional dose–response functions and showed the feasibility of an experimental, multiple‐stressor study in a wild system in which individual health status can be used as an integrator of prior stressor exposure. This approach has broad implications for other species that are difficult to handle experimentally. The quantification and management of the cumulative risk from multiple stressors on wildlife will require a combination of empirical and mechanistic approaches to inform long‐term, population consequences.

An unexpected assemblage: Moissanite and carbonaceous material from SSZ mantle rocks of the Dun Mountain Ophiolite, New Zealand - Aerona Moore; Jonathan C. Aitchison; Andreas Hertwig; Trevor R. Ireland; Ashley Locke; Axel K. Schmitt; Renjie Zhou (Contributions to Mineralogy and Petrology, 2026)
Moissanite (SiC) and other super-reducing minerals have been reported from supra-subduction zone (SSZ) ophiolites, yet their origin remains controversial given the oxidized conditions expected in forearc mantle. In this study, hundreds of moissanite grains have been recovered from mantle rocks of the Early Permian Dun Mountain Ophiolite, New Zealand. We report the first occurrence of moissanite found in direct association with disordered carbonaceous material (CM), which records low peak formation temperatures of < 334 °C. Carbon isotope analyses reveal characteristic light compositions for both moissanite (δ¹³C = − 33.7 to − 19.2‰; mean − 25.0‰) and associated CM (δ¹³C = -39.2 to -29.0‰; mean − 35.3‰). The light C isotope signatures of both phases are consistent with moissanite formation via fractionation of ultra-reduced, carbon-rich fluids derived from organic-rich sediments carried by a subducting lithospheric slab. Preservation of moissanite in an oxidized forearc mantle could be aided by low temperatures and relatively short mantle residence times. Whilst the total mass of moissanite formed under these settings is low, these findings highlight the occurrence of localised ultra-reducing conditions at shallow depths in SSZ environments and identify an under-recognised pathway for carbon cycling in subduction zones.

The Integration of Fire Ecology and Freshwater Ecosystems in North America: Knowledge Gaps and Research Needs - Morgan L. Piczak; Ava J. A. Sergio; Caliyena R. Brown; Waverley S. Birch; Rebecca L. Flitcroft; Meg A. Krawchuk; Colin P. R. McCarter; Jonathan W. Moore; Brendan P. Murphy; Brooke E. Penaluna; Prabha A. Rupasinghe; Victoria Steblaj; et al. (Global Change Biology, 2026)
Wildfires, unplanned fires that start and spread under the influence of weather and fuel composition, are increasing in frequency, duration, and severity across North America. While wildfires are one component of wildland fire, a broader natural process in many ecosystems, their changing behavior poses growing ecological and management challenges. Although wildfire is widely recognized as an important disturbance, empirical research quantifying its impacts on freshwater ecosystems remains limited and fragmented. As a result, our understanding of how wildfire affects imperiled freshwater systems remains underdeveloped. The objective of this review was to synthesize the existing empirical literature and identify key knowledge gaps to guide future research on wildfire–freshwater interactions across both biotic and abiotic components. At the biological scale, uncertainties remain around species‐ and community‐level responses (e.g., direct and indirect effects on biota). Freshwater habitat dimensions should also be the focus of further research, including alterations to physical structure (e.g., vegetation) and physicochemical conditions (e.g., temperature). From a management perspective, critical questions relate to fire‐informed restoration (e.g., specialized techniques, role of managed burns) and strategies for enhancing ecosystem resilience (e.g., identifying relevant indicators, links to watershed health). Understanding how land‐use change (e.g., forestry) and climate change interact to influence wildfire regimes and generate cumulative effects across landscapes is also essential in this new wildfire reality. To advance research and practice, we recommend comprehensive monitoring, standardization of methods and indicators, recognition of the role of cultural and prescribed burns, meaningful knowledge co‐production, and bridging the gap between scientific knowledge and management action.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Genetic Diversity Impacts Climate‐Induced Species Range Shifts - Brunno F. Oliveira; Romain Bertrand; Lise Comte; Jonathan Lenoir; Gaël Grenouillet; Lesley T. Lancaster; Jérôme Murienne; Sarah Diamond; Brett R. Scheffers; R. M. W. J. Bandara; Jake A. Lawlor; Nikki A. Moore; et al. (Ecology Letters, 2026)
Climate change threatens biodiversity when species cannot tolerate, adapt to, or track shifting environmental conditions to stay within their climatic niches. A major unresolved question is whether and how species' genetic diversity modulates these dynamics, buffering against range contractions or facilitating range expansions. To test this, we integrated the largest global databases of species range shifts and genetic diversity, encompassing 4673 range shift estimates for 1888 species with available genetic data, including insects, arachnids, birds, fish, and plants. We found that range shifting rates were significantly shaped by the interaction of genetic diversity and climate change velocity. Under rapid warming, species with higher genetic diversity exhibited reduced trailing edge contractions, likely reflecting enhanced evolutionary potential or reduced vulnerability to drift. Under moderate warming, species with higher genetic diversity shifted more rapidly at leading edges and range centroids, consistent with greater colonisation ability. Our study provides evidence that genetic diversity potentially enables persistence at the trailing edge and colonisation at the leading edge, with the magnitude of these effects varying depending on the velocity of climate change.

Editorial: Turning with the tide and time in the Salish Sea: change in estuary and nearshore habitats and species dependent on them - Correigh M. Greene; Julie S. Barber; Joshua W. Chamberlin; Phoebe L. Gross; Jonathan W. Moore; Letitita (Tish) Conway-Cranos; Michael T. LeMoine; Kathryn L. Sobocinski; Elene Trujillo (Frontiers in Marine Science, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

A Safe Operating Space for Salmon Watersheds Under Rapid Climate Change - Jonathan W. Moore; Marta E. Ulaski; Kyle L. Wilson; Tara G. Martin; Spencer Dakin Kuiper; Stephanie J. Peacock; Douglas C. Braun; Sean M. Naman; Kara J. Pitman; Andrea J. Reid; Jordan S. Rosenfeld; Nigel C. Sainsbury; et al. (Fish and Fisheries, 2025)
Climate change and local pressures are eroding the health and performance of many watersheds and their freshwater ecosystems, pushing these complex social‐ecological systems to the boundaries of their safe operating space. Here, we offer a synthetic perspective on the downscaled application of the safe operating space concept to inform the stewardship of watersheds in this time of rapid climate change, with particular focus on watersheds that support coldwater migratory fishes such as Pacific salmon. First, we review the safe operating space concept as it applies to salmon watersheds as social‐ecological systems. Salmon watersheds, and the benefits they provide for diverse peoples, are under enormous cumulative pressure from climate change as well as local activities such as forestry, urbanisation, mining and agriculture. We identify four general syndromes of dual local and climate pressures. For example, local pressures, such as the removal of riparian vegetation that shades streams, can exacerbate climate warming of water temperatures. Furthermore, extractive industries can damage or destroy future habitats and thus erode adaptive capacity. As an illustrative example of how the safe operating space concept can be operationalised, we assess alternative plausible watershed futures of land use and climate change scenarios and salmon performance. Collectively, this work showcases tangible options for local management to help give salmon watersheds the time and space to cope with climate change. More broadly, while there is a global need to address climate change, local watershed management is a key component of pathways towards freshwater sustainability and their services for humanity.

Probing the mechanisms of Fe(III)/As(V) reduction and As mobilisation using mineral-coated sands; impact of electron donor treatments - Oliver C. Moore; Laura A. Richards; Christopher Boothman; Sam Shaw; Babajide Milton Macaulay; David A. Polya; Bart E. van Dongen; Jonathan R. Lloyd (Science of The Total Environment, 2025)

Species characteristics modulate tropical mammal responses to forest quality in Southeast Asia - Pradeep Raj Joshi; Asunción Semper-Pascual; Andrea F. Vallejo-Vargas; Douglas Sheil; Matthew S. Luskin; Jonathan Moore; Richard Bischof (Biological Conservation, 2025)

The Seaward Migration of European Eel at a Continental Scale: A Europe‐Wide Biotelemetry Meta‐Analysis - Pieterjan Verhelst; David Righton; Kim Aarestrup; Pedro R. Almeida; Tea Bašić; Jonathan D. Bolland; Liam Carter; Johan Coeck; José Lino Costa; Justas Dainys; Jan Grimsrud Davidsen; Isabel Domingos; et al. (Fish and Fisheries, 2025)
The European eel ( Anguilla anguilla L.) has a catadromous life cycle, with a single panmictic population that colonises continental Europe and northern Africa yet migrates 5000 to 9000 km to spawn in the Atlantic Ocean. It is unknown how this continental migration is organised so individual eels arrive in time for spawning with conspecifics. This meta‐analysis combined tracking data from 18 water bodies in freshwater and transitional systems distributed along the southwest‐northeast axis of Europe, resulting in a dataset of 2306 eels, making it the most comprehensive in terms of geographical coverage and number of eels tagged. The eels were tracked using acoustic telemetry and the Nedap Trail System and allowed us to study the eel's migration phenology at a continental scale. The findings reveal that the day when eels arrive at sea varies significantly with latitude, with northern eels arriving earlier. Migration speed differs between tidal and non‐tidal habitats, suggesting that tidal currents facilitate faster movement. However, despite these patterns, we observed substantial variability in arrival at sea time and migration speed within water bodies, suggesting that the eel's migration phenology is considerably plastic. The presence of water regulating structures such as weirs, pumping stations and hydropower plants can impact migration timing and speed, potentially delaying eels, but is likely dependent on local hydrological conditions which can be water body specific.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Surfing the tidal wave: Use of transiently aquatic habitat by juvenile Pacific salmon and other fishes in estuaries - Daniel J. Scurfield; Phoebe L. Gross; Julian C. L. Gan; Jonathan W. Moore (Ecology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Characterisation of dissolved organic matter in two contrasting arsenic-prone sites in Kandal Province, Cambodia - Oliver C. Moore; Amy D. Holt; Laura A. Richards; Amy M. McKenna; Robert G.M. Spencer; Dan J. Lapworth; David A. Polya; Jonathan R. Lloyd; Bart E. van Dongen (Organic Geochemistry, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

The murine metastatic microenvironment of experimental brain metastases of breast cancer differs by host age in vivo: a proteomic study - Allison L. Hunt; Imran Khan; Alex M. L. Wu; Sasha C. Makohon-Moore; Brian L. Hood; Kelly A. Conrads; Tamara Abulez; Jonathan Ogata; Dave Mitchell; Glenn Gist; Julie Oliver; Debbie Wei; et al. (Clinical & Experimental Metastasis, 2024)

CamTrapAsia : A dataset of tropical forest vertebrate communities from 239 camera trapping studies - Calebe P. Mendes; Wido R. Albert; Zachary Amir; Marc Ancrenaz; Eric Ash; Badrul Azhar; Henry Bernard; Jedediah Brodie; Tom Bruce; Elliot Carr; Gopalasamy Reuben Clements; Glyn Davies; et al. (Ecology, 2024)
Information on tropical Asian vertebrates has traditionally been sparse, particularly when it comes to cryptic species inhabiting the dense forests of the region. Vertebrate populations are declining globally due to land‐use change and hunting, the latter frequently referred as “defaunation.” This is especially true in tropical Asia where there is extensive land‐use change and high human densities. Robust monitoring requires that large volumes of vertebrate population data be made available for use by the scientific and applied communities. Camera traps have emerged as an effective, non‐invasive, widespread, and common approach to surveying vertebrates in their natural habitats. However, camera‐derived datasets remain scattered across a wide array of sources, including published scientific literature, gray literature, and unpublished works, making it challenging for researchers to harness the full potential of cameras for ecology, conservation, and management. In response, we collated and standardized observations from 239 camera trap studies conducted in tropical Asia. There were 278,260 independent records of 371 distinct species, comprising 232 mammals, 132 birds, and seven reptiles. The total trapping effort accumulated in this data paper consisted of 876,606 trap nights, distributed among Indonesia, Singapore, Malaysia, Bhutan, Thailand, Myanmar, Cambodia, Laos, Vietnam, Nepal, and far eastern India. The relatively standardized deployment methods in the region provide a consistent, reliable, and rich count data set relative to other large‐scale pressence‐only data sets, such as the Global Biodiversity Information Facility (GBIF) or citizen science repositories (e.g., iNaturalist), and is thus most similar to eBird. To facilitate the use of these data, we also provide mammalian species trait information and 13 environmental covariates calculated at three spatial scales around the camera survey centroids (within 10‐, 20‐, and 30‐km buffers). We will update the dataset to include broader coverage of temperate Asia and add newer surveys and covariates as they become available. This dataset unlocks immense opportunities for single‐species ecological or conservation studies as well as applied ecology, community ecology, and macroecology investigations. The data are fully available to the public for utilization and research. Please cite this data paper when utilizing the data.

Bringing traits back into the equation: A roadmap to understand species redistribution - Lise Comte; Romain Bertrand; Sarah Diamond; Lesley T. Lancaster; Malin L. Pinsky; Brett R. Scheffers; J. Alex Baecher; R. M. W. J. Bandara; I‐Ching Chen; Jake A. Lawlor; Nikki A. Moore; Brunno F. Oliveira; et al. (Global Change Biology, 2024)
Ecological and evolutionary theories have proposed that species traits should be important in mediating species responses to contemporary climate change; yet, empirical evidence has so far provided mixed evidence for the role of behavioral, life history, or ecological characteristics in facilitating or hindering species range shifts. As such, the utility of trait‐based approaches to predict species redistribution under climate change has been called into question. We develop the perspective, supported by evidence, that trait variation, if used carefully can have high potential utility, but that past analyses have in many cases failed to identify an explanatory value for traits by not fully embracing the complexity of species range shifts. First, we discuss the relevant theory linking species traits to range shift processes at the leading (expansion) and trailing (contraction) edges of species distributions and highlight the need to clarify the mechanistic basis of trait‐based approaches. Second, we provide a brief overview of range shift–trait studies and identify new opportunities for trait integration that consider range‐specific processes and intraspecific variability. Third, we explore the circumstances under which environmental and biotic context dependencies are likely to affect our ability to identify the contribution of species traits to range shift processes. Finally, we propose that revealing the role of traits in shaping species redistribution may likely require accounting for methodological variation arising from the range shift estimation process as well as addressing existing functional, geographical, and phylogenetic biases. We provide a series of considerations for more effectively integrating traits as well as extrinsic and methodological factors into species redistribution research. Together, these analytical approaches promise stronger mechanistic and predictive understanding that can help society mitigate and adapt to the effects of climate change on biodiversity.

David versus Goliath: Early career researchers in an unethical publishing system - Aurore Receveur; Jonathan Bonfanti; Stephanie D'Agata; Andrew J. Helmstetter; Nikki A. Moore; Brunno F. Oliveira; Cathleen Petit‐Cailleux; Erica Rievrs Borges; Marieke Schultz; Aaron N. Sexton; Devi Veytia (Ecology Letters, 2024)
The publish‐or‐perish culture in academia has catalysed the development of an unethical publishing system. This system is characterised by the proliferation of journals and publishers—unaffiliated with learned societies or universities—that maintain extremely large revenues and profit margins diverting funds away from the academic community. Early career researchers (ECRs) are particularly vulnerable to the consequences of this publishing system because of intersecting factors, including pressure to pursue high impact publications, rising publication costs and job insecurity. Moving towards a more ethical system requires that scientists advocate for structural change by making career choices that come with risks, many of which disproportionately impact ECRs. We illuminate major issues facing ECRs in Ecology and Evolution under the current publishing system, and propose a portfolio of actions to promote systemic change that can be implemented by ECRs and established researchers.

An interdisciplinary synthesis of floodplain ecosystem dynamics in a rapidly deglaciating watershed - Christopher J. Sergeant; Jonathan W. Moore; Diane C. Whited; Kara J. Pitman; Mark Connor; Erin K. Sexton (Science of The Total Environment, 2024)

Habitat modulates population‐level responses of freshwater salmon growth to a century of change in climate and competition - Michael H. H. Price; Jonathan W. Moore; Skip McKinnell; Brendan M. Connors; John D. Reynolds (Global Change Biology, 2024)
The impacts of climate change are widespread and threaten natural systems globally. Yet, within regions, heterogeneous physical landscapes can differentially filter climate, leading to local response diversity. For example, it is possible that while freshwater lakes are sensitive to climate change, they may exhibit a diversity of thermal responses owing to their unique morphology, which in turn can differentially affect the growth and survival of vulnerable biota such as fishes. In particular, salmonids are cold‐water fishes with complex life histories shaped by diverse freshwater habitats that are sensitive to warming temperatures. Here we examine the influence of habitat on the growth of sockeye salmon ( Oncorhynchus nerka ) in nursery lakes of Canada's Skeena River watershed over a century of change in regional temperature and intraspecific competition. We found that freshwater growth has generally increased over the last century. While growth tended to be higher in years with relatively higher summer air temperatures (a proxy for lake temperature), long‐term increases in growth appear largely influenced by reduced competition. However, habitat played an important role in modulating the effect of high temperature. Specifically, growth was positively associated with rising temperatures in relatively deep (>50 m) nursery lakes, whereas warmer temperatures were not associated with a change in growth for fish among shallow lakes. The influence of temperature on growth also was modulated by glacier extent whereby the growth of fish from lakes situated in watersheds with little (i.e.,

Complex temperature mosaics across space and time in estuaries: implications for current and future nursery function for Pacific salmon - Phoebe L. Gross; Julian C.L. Gan; Daniel J. Scurfield; Cory Frank; Cedar Frank; Caelan McLean; Chris Bob; Jonathan W. Moore (Frontiers in Marine Science, 2023)
Water temperature is a key dimension of estuaries that can influence important biological processes including organismal growth, survival, and habitat use. For example, juvenile Pacific salmon rely on temperature-mediated growth opportunities in estuaries during seaward migration in the spring and summer. However, oncoming climate change is warming estuary temperatures and transforming growth potential. Yet, it is likely that estuary water temperatures are complex and dynamic across space and time. Here we investigated spatial and temporal patterns of water temperature across two contrasting estuaries on Vancouver Island, BC, and used these data to simulate juvenile Chinook salmon growth potential under both present conditions and a simplified scenario of climate warming. Summer temperatures were warmer and more spatially homogeneous across the Englishman River estuary relative to the Salmon River estuary. Within each system, temperature was variable across habitats and sites, appearing to be driven by a combination of local climate, river and ocean temperatures, tidal fluctuations, and habitat features. This shifting mosaic of temperatures generated a complex portfolio of growth opportunities for juvenile Chinook salmon. There were broad patterns of increasing growth potential across both systems as temperatures warmed in early summer. However, excessively hot late summer temperatures drove steep declines in growth potential across the Englishman River estuary, while positive trends continued through August in the Salmon River estuary. A simple climate change scenario revealed that estuaries and habitats may have differing vulnerabilities to increasing temperatures—with climate warming, favorable growth opportunities were even more constricted to early summer in the Englishman River estuary, but expanded across most habitats and times in the Salmon River estuary given lower baseline temperatures and higher habitat complexity. Collectively, this work underscores the importance of habitat complexity and local climate for maintaining diverse growth opportunities across estuaries, which may confer resilience to the nursery function of estuaries as temperature mosaics warm.

Evaluating Alternate Methods of 4D-Var Data Assimilation in a Coupled Hydrodynamic—Four-Component Biogeochemical Model of the California Current System - Jonathan G. Izett; J. Paul Mattern; Andrew M. Moore; Christopher A. Edwards (Ocean Modelling, 2023)

Wild salmon enumeration and monitoring using deep learning empowered detection and tracking - William I. Atlas; Sami Ma; Yi Ching Chou; Katrina Connors; Daniel Scurfield; Brandon Nam; Xiaoqiang Ma; Mark Cleveland; Janvier Doire; Jonathan W. Moore; Ryan Shea; Jiangchuan Liu (Frontiers in Marine Science, 2023)
Pacific salmon have experienced declining abundance and unpredictable returns, yet remain vital to livelihoods, food security, and cultures of coastal communities around the Pacific Rim, creating a need for reliable and timely monitoring to inform sustainable fishery management. Currently, spawning salmon abundance is often monitored with in-river video or sonar cameras. However, reviewing video for estimates of salmon abundance from these programs requires thousands of hours of staff time, and data are typically not available until after the fishing season is completed. Computer vision deep learning can enable rapid and reliable processing of data, with potentially transformative applications in salmon population assessment and fishery management. Working with two First Nations fishery programs in British Columbia, Canada, we developed, trained, and tested deep learning models to perform object detection and multi-object tracking for automated video enumeration of salmon passing two First Nation-run weirs. We gathered and annotated more than 500,000 frames of video data encompassing 12 species, including seven species of anadromous salmonids, and trained models for multi-object tracking and species detection. Our top performing model achieved a mean average precision (mAP) of 67.6%, and species-specific mAP scores > 90% for coho and > 80% for sockeye salmon when trained with a combined dataset of Kitwanga and Bear Rivers’ salmon annotations. We also tested and deployed a prototype for a real-time monitoring system that can perform computer vision deep learning analyses on site. Computer vision models and off-grid monitoring systems show promise for automated counting and species identification. A key future priority will be working with stewardship practitioners and fishery managers to apply salmon computer vision, testing and applying edge-capable computing solutions for in-situ analysis at remote sites, and developing tools for independent user-led computer vision analysis by non-computer scientists. These efforts can advance in-season monitoring and decision making to support adaptive management of sustainable wild salmon fisheries.

OME-Zarr: a cloud-optimized bioimaging file format with international community support - Josh Moore; Daniela Basurto-Lozada; Sébastien Besson; John Bogovic; Jordão Bragantini; Eva M. Brown; Jean-Marie Burel; Xavier Casas Moreno; Gustavo de Medeiros; Erin E. Diel; David Gault; Satrajit S. Ghosh; et al. (Histochemistry and Cell Biology, 2023)
A growing community is constructing a next-generation file format (NGFF) for bioimaging to overcome problems of scalability and heterogeneity. Organized by the Open Microscopy Environment (OME), individuals and institutes across diverse modalities facing these problems have designed a format specification process (OME-NGFF) to address these needs. This paper brings together a wide range of those community members to describe the cloud-optimized format itself—OME-Zarr—along with tools and data resources available today to increase FAIR access and remove barriers in the scientific process. The current momentum offers an opportunity to unify a key component of the bioimaging domain—the file format that underlies so many personal, institutional, and global data management and analysis tasks.

Improving data collection in pregnancy safety studies: Towards standardization of data elements in pregnancy reports from public and private partners (ConcePTION) - Guillaume Favre; Jonathan L. Richardson; Alan Moore; Yvonne Geissbühler; Valentine Jehl; Alison Oliver; Svetlana Shechtman; Orna Diav-Citrin; Maya Berlin; Tal De-Haan; Anil Mor; Meritxell Sabidó; et al. (Neurotoxicology and Teratology, 2023)

IMI ConcePTION core data elements for pregnancy pharmacovigilance studies using primary source data collection methods - Jonathan Richardson; Alan Moore; Rebecca Bromley; Michael Stellfeld; Yvonne Geissbühler; Matthew Bluett-Duncan; Ursula Winterfeld; Guillaume Favre; Kenneth Hodson; Alison Oliver; Amalia Alexe; Yrea van Rijt-Weetink; et al. (Neurotoxicology and Teratology, 2023)

Mid-sized felids threatened by habitat degradation in Southeast Asia - Henri Decœur; Zachary Amir; Calebe P. Mendes; Jonathan H. Moore; Matthew Scott Luskin (Biological Conservation, 2023)

Trends in Chinook salmon spawner abundance and total run size highlight linkages between life history, geography and decline - William I. Atlas; Matthew R. Sloat; William H. Satterthwaite; Thomas W. Buehrens; Charles K. Parken; Jonathan W. Moore; Nathan J. Mantua; Jon Hart; Anna Potapova (Fish and Fisheries, 2023)
Chinook salmon ( Oncorhynchus tshawytscha , Salmonidae) are foundational to social‐ecological systems of the Northeast Pacific Rim and exhibit a rich diversity of life histories including in their adult migration timing, age at critical life‐history transitions and marine feeding distributions. In recent decades Chinook have experienced declines across much of their native range; however, changes in productivity and abundance have rarely been evaluated in relation to life‐history variation. To understand trends in Chinook salmon production, and how they are related to life history, we compiled time series data from the Fraser River to the Sacramento River on total run size (pre‐fishery abundance) and escapement (post‐fishery spawner abundance) and fit time series models to estimate trends across this bioregion. Our analysis revealed that most Chinook populations are declining, with negative trends in escapement (57 of 79) and total run (16 of 23) size. Trends were most acutely negative for interior spring Chinook in the Fraser, Columbia and Snake Rivers and most populations in California. Summer and fall Chinook had mixed trends, with several summer and fall upriver bright populations in the interior Columbia and Fraser exhibiting increases in abundance from the 1990s to 2019. Our research reveals widespread declines of this important species, but local complexity in trends that are mediated by population‐level life history, migratory behaviours and watershed‐scale restoration actions. Understanding linkages between life histories and resilience should inform rebuilding efforts for Chinook salmon and highlight the need to conserve intraspecific biodiversity.

COVID-19, Climate Change, and Conflict in Honduras: A food system disruption analysis - Jonathan Lara-Arévalo; Lucía Escobar-Burgos; E.R.H. Moore; Roni Neff; Marie L. Spiker (Global Food Security, 2023)

Foraging guild modulates insectivorous bat responses to habitat loss and insular fragmentation in peninsular Malaysia - Quentin C.K. Hazard; Jérémy S.P. Froidevaux; Natalie Yoh; Jonathan Moore; Juliana Senawi; Luke Gibson; Ana Filipa Palmeirim (Biological Conservation, 2023)

The role of electron donors in arsenic-release by redox-transformation of iron oxide minerals – A review - Oliver C. Moore; Wei Xiu; Huaming Guo; David A. Polya; Bart E. van Dongen; Jonathan R. Lloyd (Chemical Geology, 2023)

Health Literacy Correlates to HPV Vaccination Among US Adults Ages 27–45 - Annalynn M. Galvin; Ashvita Garg; Stacey B. Griner; Jonathan D. Moore; Erika L. Thompson (Journal of Cancer Education, 2023)

Age- and time-dependent mitochondrial genotoxic and myopathic effects of beta-guanidinopropionic acid, a creatine analog, on rodent skeletal muscles - Allen Herbst; Judd M. Aiken; Chiye Kim; Danielle Gushue; Debbie McKenzie; Timothy M. Moore; Jin Zhou; Austin N. Hoang; Solbie Choi; Jonathan Wanagat (GeroScience, 2023)

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Long-term Annual Aerial Surveys of Submersed Aquatic Vegetation (SAV) Support Science, Management, and Restoration - Robert J. Orth; William C. Dennison; Cassie Gurbisz; Michael Hannam; Jeni Keisman; J. Brooke Landry; Jonathan S. Lefcheck; Kenneth A. Moore; Rebecca R. Murphy; Christopher J. Patrick; Jeremy Testa; Donald E. Weller; et al. (Estuaries and Coasts, 2022)
Aerial surveys of coastal habitats can uniquely inform the science and management of shallow, coastal zones, and when repeated annually, they reveal changes that are otherwise difficult to assess from ground-based surveys. This paper reviews the utility of a long-term (1984–present) annual aerial monitoring program for submersed aquatic vegetation (SAV) in Chesapeake Bay, its tidal tributaries, and nearby Atlantic coastal bays, USA. We present a series of applications that highlight the program’s importance in assessing anthropogenic impacts, gauging water quality status and trends, establishing and evaluating restoration goals, and understanding the impact of commercial fishing practices on benthic habitats. These examples demonstrate how periodically quantifying coverage of this important foundational habitat answers basic research questions locally, as well as globally, and provides essential information to resource managers. New technologies are enabling more frequent and accurate aerial surveys at greater spatial resolution and lower cost. These advances will support efforts to extend the applications described here to similar issues in other areas.

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Cover and density of southwestern ponderosa pine understory plants in permanent chart quadrats (2002–2020) - Margaret M. Moore; Jeffrey S. Jenness; Daniel C. Laughlin; Robert T. Strahan; Jonathan D. Bakker; Helen E. Dowling; Judith D. Springer (Ecology, 2022)
This data set consists of 101 permanent 1 m × 1 m (1‐m 2 ) quadrats located within southwestern ponderosa pine ecosystems near Flagstaff, Arizona, USA. Individual plants in these quadrats were identified and mapped annually for 19 years (2002–2020). The original chart quadrats were established between 1912 and 1927 to determine the effects of domestic livestock grazing on herbaceous plants and pine seedlings. Today these data provide opportunities to examine the effects of climate and land‐use change on plant demography, population dynamics, and community processes. We provide the following data and data formats: (1) digitized maps of all plant locations in shapefile and geodatabase format, (2) shapefiles showing annual locations of each individual plant species, (3) annual maps of each quadrat in TIFF and PDF format, (4) annual basal area of each species per quadrat for species mapped as polygons, (5) tabular representation of polygon areas and centroid locations for plant species mapped as polygons, (6) tabular representation of point locations for plant species mapped as points, (7) plot‐scale 20 m × 20 m overstory tree canopy cover, tree basal area, parent material, and elevation, (8) quadrat‐scale information (e.g., quadrat site and number, coordinates in UTM Zone 12 and latitude/longitude, and descriptive comments for each quadrat), (9) plant species list, (10) summary of plant species observed in each quadrat, (11) summary of quadrats mapped by site and year, and (12) data formatted for use in Integral Projection Models (IPM) and plant population analyses. There are no copyright restrictions; please cite this paper and the associated data set when data are used in publications.

Nutrient identity modifies the destabilising effects of eutrophication in grasslands - Oliver Carroll; Evan Batzer; Siddharth Bharath; Elizabeth T. Borer; Sofía Campana; Ellen Esch; Yann Hautier; Timothy Ohlert; Eric W. Seabloom; Peter B. Adler; Jonathan D. Bakker; Lori Biederman; et al. (Ecology Letters, 2022)
Nutrient enrichment can simultaneously increase and destabilise plant biomass production, with co‐limitation by multiple nutrients potentially intensifying these effects. Here, we test how factorial additions of nitrogen (N), phosphorus (P) and potassium with essential nutrients (K+) affect the stability (mean/standard deviation) of aboveground biomass in 34 grasslands over 7 years. Destabilisation with fertilisation was prevalent but was driven by single nutrients, not synergistic nutrient interactions. On average, N‐based treatments increased mean biomass production by 21–51% but increased its standard deviation by 40–68% and so consistently reduced stability. Adding P increased interannual variability and reduced stability without altering mean biomass, while K+ had no general effects. Declines in stability were largest in the most nutrient‐limited grasslands, or where nutrients reduced species richness or intensified species synchrony. We show that nutrients can differentially impact the stability of biomass production, with N and P in particular disproportionately increasing its interannual variability.

Aortic haemodynamics: the effects of habitual endurance exercise, age and muscle sympathetic vasomotor outflow in healthy men - Denis J. Wakeham; Tony G. Dawkins; Rachel N. Lord; Jack S. Talbot; Freya M. Lodge; Bryony A. Curry; Lydia L. Simpson; Christopher J. A. Pugh; Robert E. Shave; Jonathan P. Moore (European Journal of Applied Physiology, 2022)
Purpose We determined the effect of habitual endurance exercise and age on aortic pulse wave velocity (aPWV), augmentation pressure (AP) and systolic blood pressure (aSBP), with statistical adjustments of aPWV and AP for heart rate and aortic mean arterial pressure, when appropriate. Furthermore, we assessed whether muscle sympathetic nerve activity (MSNA) correlates with AP in young and middle-aged men. Methods Aortic PWV, AP, aortic blood pressure (applanation tonometry; SphygmoCor) and MSNA (peroneal microneurography) were recorded in 46 normotensive men who were either young or middle-aged and endurance-trained runners or recreationally active nonrunners (10 nonrunners and 13 runners within each age-group). Between-group differences and relationships between variables were assessed via ANOVA/ANCOVA and Pearson product-moment correlation coefficients, respectively. Results Adjusted aPWV and adjusted AP were similar between runners and nonrunners in both age groups (all, P > 0.05), but higher with age (all, P < 0.001), with a greater effect size for the age-related difference in AP in runners (Hedges’ g , 3.6 vs 2.6). aSBP was lower in young ( P = 0.009; g = 2.6), but not middle-aged ( P = 0.341; g = 1.1), runners compared to nonrunners. MSNA burst frequency did not correlate with AP in either age group (young: r = 0.00, P = 0.994; middle-aged: r = − 0.11, P = 0.604). Conclusion There is an age-dependent effect of habitual exercise on aortic haemodynamics, with lower aSBP in young runners compared to nonrunners only. Statistical adjustment of aPWV and AP markedly influenced the outcomes of this study, highlighting the importance of performing these analyses. Further, peripheral sympathetic vasomotor outflow and AP were not correlated in young or middle-aged normotensive men.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Marine and freshwater regime changes impact a community of migratory Pacific salmonids in decline - Kyle L. Wilson; Colin J. Bailey; Trevor D. Davies; Jonathan W. Moore (Global Change Biology, 2022)
Marine and freshwater ecosystems are increasingly at risk of large and cascading changes from multiple human activities (termed “regime shifts”), which can impact population productivity, resilience, and ecosystem structure. Pacific salmon exhibit persistent and large fluctuations in their population dynamics driven by combinations of intrinsic (e.g., density dependence) and extrinsic factors (e.g., ecosystem changes, species interactions). In recent years, many Pacific salmon have declined due to regime shifts but clear understanding of the processes driving these changes remains elusive. Here, we unpacked the role of density dependence, ecosystem trends, and stochasticity on productivity regimes for a community of five anadromous Pacific salmonids (Steelhead, Coho Salmon, Pink Salmon, Dolly Varden, and Coastal Cutthroat Trout) across a rich 40‐year time‐series. We used a Bayesian multivariate state‐space model to examine whether productivity shifts had similarly occurred across the community and explored marine or freshwater changes associated with those shifts. Overall, we identified three productivity regimes: an early regime (1976–1990), a compensatory regime (1991–2009), and a declining regime (since 2010) where large declines were observed for Steelhead, Dolly Varden, and Cutthroat Trout, intermediate declines in Coho and no change in Pink Salmon. These regime changes were associated with multiple cumulative effects across the salmon life cycle. For example, increased seal densities and ocean competition were associated with lower adult marine survival in Steelhead. Watershed logging also intensified over the past 40 years and was associated with (all else equal) ≥97% declines in freshwater productivity for Steelhead, Cutthroat, and Coho. For Steelhead, marine and freshwater dynamics played approximately equal roles in explaining trends in total productivity. Collectively, these changing environments limited juvenile production and lowered future adult returns. These results reveal how changes in freshwater and marine environments can jointly shape population dynamics among ecological communities, like Pacific salmon, with cascading consequences to their resilience.

Temporal rarity is a better predictor of local extinction risk than spatial rarity - Peter A. Wilfahrt; Ashley L. Asmus; Eric W. Seabloom; Jeremiah A. Henning; Peter Adler; Carlos A. Arnillas; Jonathan D. Bakker; Lori Biederman; Lars A. Brudvig; Marc Cadotte; Pedro Daleo; Anu Eskelinen; et al. (Ecology, 2021)
Spatial rarity is often used to predict extinction risk, but rarity can also occur temporally. Perhaps more relevant in the context of global change is whether a species is core to a community (persistent) or transient (intermittently present), with transient species often susceptible to human activities that reduce niche space. Using 5–12 yr of data on 1,447 plant species from 49 grasslands on five continents, we show that local abundance and species persistence under ambient conditions are both effective predictors of local extinction risk following experimental exclusion of grazers or addition of nutrients; persistence was a more powerful predictor than local abundance. While perturbations increased the risk of exclusion for low persistence and abundance species, transient but abundant species were also highly likely to be excluded from a perturbed plot relative to ambient conditions. Moreover, low persistence and low abundance species that were not excluded from perturbed plots tended to have a modest increase in abundance following perturbance. Last, even core species with high abundances had large decreases in persistence and increased losses in perturbed plots, threatening the long‐term stability of these grasslands. Our results demonstrate that expanding the concept of rarity to include temporal dynamics, in addition to local abundance, more effectively predicts extinction risk in response to environmental change than either rarity axis predicts alone.

The role of large, glaciated tributaries in cooling an important Pacific salmon migration corridor: a study of the Babine River - Kara J. Pitman; Jonathan W. Moore (Environmental Biology of Fishes, 2021)

Species loss due to nutrient addition increases with spatial scale in global grasslands - Eric W. Seabloom; Evan Batzer; Jonathan M. Chase; W. Stanley Harpole; Peter B. Adler; Sumanta Bagchi; Jonathan D. Bakker; Isabel C. Barrio; Lori Biederman; Elizabeth H. Boughton; Miguel N. Bugalho; Maria C. Caldeira; et al. (Ecology Letters, 2021)
The effects of altered nutrient supplies and herbivore density on species diversity vary with spatial scale, because coexistence mechanisms are scale dependent. This scale dependence may alter the shape of the species–area relationship (SAR), which can be described by changes in species richness ( S ) as a power function of the sample area ( A ): S = cA z , where c and z are constants. We analysed the effects of experimental manipulations of nutrient supply and herbivore density on species richness across a range of scales (0.01–75 m 2 ) at 30 grasslands in 10 countries. We found that nutrient addition reduced the number of species that could co‐occur locally, indicated by the SAR intercepts (log c ), but did not affect the SAR slopes ( z ). As a result, proportional species loss due to nutrient enrichment was largely unchanged across sampling scales, whereas total species loss increased over threefold across our range of sampling scales.

Effect of Poultry Manure Compost and Arbuscular Mycorrhizal Fungi on Cu Immobilization and Soil Microbial Communities in a Cu-Contaminated Soil Using the Metallophyte Oenothera Picensis - Sebastián Meier; Francisca Moore; Nasser Khan; María-Eugenia González; Jorge Medina; Jonathan Cumming; Arturo Morales; Paola Durán; Alex Seguel; Humberto Aponte (Journal of Soil Science and Plant Nutrition, 2021)

Conservation risks and portfolio effects in mixed‐stock fisheries - Jonathan W. Moore; Brendan M. Connors; Emma E. Hodgson (Fish and Fisheries, 2021)
Fish biodiversity sustains the resilience and productivity of fisheries, yet this biodiversity can be threatened by overharvest and depletion in mixed‐stock fisheries. Thus, the biodiversity that provides benefits may also make sustainable resource extraction more difficult, a key challenge in fisheries management. We simulated a mixed‐stock fishery to explore relationships between different dimensions of biodiversity and fishery performance relative to conservation and fishery objectives. Different dimensions of biodiversity (number of stocks, evenness, asynchrony among stocks, heterogeneity in stock productivity) exacerbated trade‐offs between fishery and conservation objectives. For example, fisheries targeting stock‐complexes with greater asynchrony, and to a lesser extent richness, had greater stability in harvest through time but also greater risks of overfishing weak stocks and reduced yield compared to less biodiverse stock‐complexes. These trade‐offs were ameliorated by increasing management control—the capacity of fishery managers to harvest specific stocks. To explore these trade‐offs in real‐world fisheries, we contrasted the fishing and population status of individual stocks within three major mixed‐stock sockeye salmon ( Oncorhynchus nerka , Salmonidae) fisheries—Bristol Bay, Fraser River, and Skeena River. In general, the fisheries with lower management control had individual stocks that were more often being over‐ or under‐fished, compared with those with higher management control, though variation among regions in biodiversity, scale of management, and magnitude of habitat alteration likely also contribute to these relationships. Collectively, our findings emphasize that there is a need to extract less or regulate better in order to conserve and benefit from biodiversity in fisheries and other natural resource management systems.

An exploratory study to investigate the association between age, physical activity, femoral trochlear cartilage thickness and biomarkers of tissue metabolism in adult males - Harry M. Roberts; Claire L. Griffith-McGeever; Julian A. Owen; Lewis Angell; Jonathan P. Moore; Jeanette M. Thom (European Journal of Applied Physiology, 2021)
Purpose To investigate the association between age, physical activity, femoral trochlear cartilage thickness and biomarkers of tissue metabolism in a cross-sectional sample of adult males. This study utilizes several emerging biomarkers that have been associated with early joint degenerative changes; serum COMP (cartilage oligomeric matrix protein), HA (hyaluronan) and lubricin. Methods Eighty-one males (age: mean (range): 43(18–70) years; body mass index: 25.2 (21.0–30.6) kg/m 2 ) volunteered. Resting serum COMP, HA and lubricin concentrations were determined via commercially available enzyme-linked immunosorbent assay (ELISA) and femoral trochlear cartilage thickness via supra-patellar ultrasound imaging. Physical activity levels were assessed using questionnaires. Statistical analyses were performed using correlation and regression analyses. Results Age was correlated with lateral trochlear cartilage thickness ( r = − 0.372; p < 0.01) and serum COMP ( r = 0.342; p < 0.01). 7-day physical activity was correlated with serum COMP ( r = 0.357, p < 0.01), and 12-month physical activity with both lateral trochlear cartilage thickness ( r = 0.340, p = 0.01) and serum HA ( r = 0.296, p < 0.05). Regression analyses revealed that age significantly accounted for the variability in lateral cartilage thickness and serum COMP, following the adjustment for potential cofounders. However, the association between age and lateral trochlear cartilage thickness was not moderated by physical activity levels (all p > 0.05). Conclusion This study indicates that older age may be associated with thinner lateral trochlear cartilage and higher cartilage turnover. Being physically active may also be positive for lateral trochlear cartilage thickness. However, overall, both age and physical activity level only account for a small amount of the variability in cartilage thickness and serum biomarkers.

A Case Study in Connecting Fisheries Management Challenges With Models and Analysis to Support Ecosystem-Based Management in the California Current Ecosystem - Desiree Tommasi; Yvonne deReynier; Howard Townsend; Chris J. Harvey; William H. Satterthwaite; Kristin N. Marshall; Isaac C. Kaplan; Stephanie Brodie; John C. Field; Elliott L. Hazen; Stefan Koenigstein; Joshua Lindsay; et al. (Frontiers in Marine Science, 2021)
One of the significant challenges to using information and ideas generated through ecosystem models and analyses for ecosystem-based fisheries management is the disconnect between modeling and management needs. Here we present a case study from the U.S. West Coast, the stakeholder review of NOAA’s annual ecosystem status report for the California Current Ecosystem established by the Pacific Fisheries Management Council’s Fisheries Ecosystem Plan, showcasing a process to identify management priorities that require information from ecosystem models and analyses. We then assess potential ecosystem models and analyses that could help address the identified policy concerns. We screened stakeholder comments and found 17 comments highlighting the need for ecosystem-level synthesis. Policy needs for ecosystem science included: (1) assessment of how the environment affects productivity of target species to improve forecasts of biomass and reference points required for setting harvest limits, (2) assessment of shifts in the spatial distribution of target stocks and protected species to anticipate changes in availability and the potential for interactions between target and protected species, (3) identification of trophic interactions to better assess tradeoffs in the management of forage species between the diet needs of dependent predators, the resilience of fishing communities, and maintenance of the forage species themselves, and (4) synthesis of how the environment affects efficiency and profitability in fishing communities, either directly via extreme events (e.g., storms) or indirectly via climate-driven changes in target species availability. We conclude by exemplifying an existing management process established on the U.S. West Coast that could be used to enable the structured, iterative, and interactive communication between managers, stakeholders, and modelers that is key to refining existing ecosystem models and analyses for management use.

Elevated levels of sulfur, nitrogen, and fluoride in small coastal streams near an aluminum smelter in north coastal British Columbia: a reply - R. Paul Weidman; Timothy J. Maguire; Jonathan W. Moore; Scott O. C. Mundle; Daniel T. Selbie (Environmental Monitoring and Assessment, 2021)

Effects of three biochars on copper immobilization and soil microbial communities in a metal-contaminated soil using a metallophyte and two agricultural plants - Sebastián Meier; Francisca Moore; María-Eugenia González; Jorge Medina; Pedro Campos; Naser Khan; Jonathan Cumming; Mario Sanhueza; Jaime Mejías; Arturo Morales; Juan Hirzel; Alex Seguel (Environmental Geochemistry and Health, 2021)

Ontogenetic habitat shifts and vulnerability: lake-outlet-spawning sockeye salmon (Oncorhynchus nerka) sensitivity to habitat connectivity and hydrologic change - Elissa K. Sweeney-Bergen; Donna Macintyre; Jonathan W. Moore (Environmental Biology of Fishes, 2021)

Source of saline groundwater on tidally influenced blue holes on San Salvador Island, Bahamas - Megan E. Smith; Jonathan G. Wynn; Robert J. Scharping; Evan W. Moore; James R. Garey; Bogdan P. Onac (Hydrogeology Journal, 2021)

Predicting biodiversity richness in rapidly changing landscapes: climate, low human pressure or protection as salvation? - David W. Macdonald; Luca Chiaverini; Helen M. Bothwell; Żaneta Kaszta; Eric Ash; Gilmoore Bolongon; Özgün Emre Can; Ahimsa Campos-Arceiz; Phan Channa; Gopalasamy Reuben Clements; Andrew J. Hearn; Laurie Hedges; et al. (Biodiversity and Conservation, 2020)
Rates of biodiversity loss in Southeast Asia are among the highest in the world, and the Indo-Burma and South-Central China Biodiversity Hotspots rank among the world’s most threatened. Developing robust multi-species conservation models is critical for stemming biodiversity loss both here and globally. We used a large and geographically extensive remote-camera survey and multi-scale, multivariate optimization species distribution modelling to investigate the factors driving biodiversity across these two adjoining biodiversity hotspots. Four major findings emerged from the work. (i) We identified clear spatial patterns of species richness, with two main biodiverse centres in the Thai-Malay Peninsula and in the mountainous region of Southwest China. (ii) Carnivores in particular, and large ungulates to a lesser degree, were the strongest indicators of species richness. (iii) Climate had the largest effect on biodiversity, followed by protected status and human footprint. (iv) Gap analysis between the biodiversity model and the current system of protected areas revealed that the majority of areas supporting the highest predicted biodiversity are not protected. Our results highlighted several key locations that should be prioritized for expanding the protected area network to maximize conservation effectiveness. We demonstrated the importance of switching from single-species to multi-species approaches to highlight areas of high priority for biodiversity conservation. In addition, since these areas mostly occur over multiple countries, we also advocate for a paradigmatic focus on transboundary conservation planning.

Using structured eradication feasibility assessment to prioritize the management of new and emerging invasive alien species in Europe - Olaf Booy; Pete A. Robertson; Niall Moore; Jess Ward; Helen E. Roy; Tim Adriaens; Richard Shaw; Johan Van Valkenburg; Gabrielle Wyn; Sandro Bertolino; Olivier Blight; Etienne Branquart; et al. (Global Change Biology, 2020)
Prioritizing the management of invasive alien species (IAS) is of global importance and within Europe integral to the EU IAS regulation. To prioritize management effectively, the risks posed by IAS need to be assessed, but so too does the feasibility of their management. While the risk of IAS to the EU has been assessed, the feasibility of management has not. We assessed the feasibility of eradicating 60 new (not yet established) and 35 emerging (established with limited distribution) species that pose a threat to the EU, as identified by horizon scanning. The assessment was carried out by 34 experts in invasion management from across Europe, applying the Non‐Native Risk Management scheme to defined invasion scenarios and eradication strategies for each species, assessing the feasibility of eradication using seven key risk management criteria. Management priorities were identified by combining scores for risk (derived from horizon scanning) and feasibility of eradication. The results show eradication feasibility score and risk score were not correlated, indicating that risk management criteria evaluate different information than risk assessment. In all, 17 new species were identified as particularly high priorities for eradication should they establish in the future, whereas 14 emerging species were identified as priorities for eradication now. A number of species considered highest priority for eradication were terrestrial vertebrates, a group that has been the focus of a number of eradication attempts in Europe. However, eradication priorities also included a diverse range of other taxa (plants, invertebrates and fish) suggesting there is scope to broaden the taxonomic range of attempted eradication in Europe. We demonstrate that broad scale structured assessments of management feasibility can help prioritize IAS for management. Such frameworks are needed to support evidence‐based decision‐making.

Impacts of industrial atmospheric emissions on watershed export of dissolved ions in coastal streams: a Bayesian modeling approach - Timothy J. Maguire; R. Paul Weidman; Scott O. C. Mundle; Jonathan W. Moore; Kyle A. Chezik; Daniel T. Selbie (Environmental Monitoring and Assessment, 2020)

Evidence for the effects of land use on freshwater ecosystems in New Zealand - Scott T. Larned; Jonathan Moores; Jenni Gadd; Brenda Baillie; Marc Schallenberg (New Zealand Journal of Marine and Freshwater Research, 2020)
To meet the challenges of preventing and reversing adverse effects of land use on ecosystems, management actions need to be founded on strong evidence. We used the pressure‐state‐impact (PSI) framework to assess evidence of land‐use effects on New Zealand freshwater ecosystems. The evidence consisted of published quantitative and categorical associations linking land‐use pressures to state changes and ecological impacts in rivers, lakes and aquifers. There was substantial evidence of land‐use effects, particularly where land use/land cover (LULC) classes were used as pressure variables. Proportions of catchment area in urban and pastoral LULC were consistently, positively correlated with contaminant levels in water bodies and negatively correlated with ecological‐health indicators. Other consistent PSI associations included positive correlations between cattle stocking rates and river contaminant levels, increased fine sediment and decreased ecological‐health scores in rivers following forest harvest, and increased river contaminant levels at sites with stock access. Despite these consistent associations, the evidence base has four general shortcomings that should be addressed: (1) inadequate integration of data and models that link land use and contaminant loss to state changes and impacts in freshwater ecosystems; (2) weak inferences based on LULC; (3) reliance on categorical PSI associations; (4) gaps in reported PSI associations.

Landscape and biophysical controls of lake productivity to inform evaluation of sockeye salmon ( Oncorhynchus nerka ) populations in data‐limited regions - William I. Atlas; Daniel T. Selbie; Carrie A. Holt; Steve Cox‐Rogers; Charmaine Carr‐Harris; Kara J. Pitman; Jonathan W. Moore (Limnology and Oceanography, 2020)
Landscape models are increasingly used to classify and predict the structure and productivity of data‐limited aquatic ecosystems. One such suite of ecosystems is on the remote North and Central Coast (NCC) of British Columbia, where sockeye salmon ( Oncorhynchus nerka ) rear in more than 150 lakes. Given their remoteness and limited resources for assessment, limnological and population monitoring in many of these lakes has been periodic or absent, limiting understanding of the status of populations and their habitats. Lake photosynthetic rate (PR) estimates are foundational to models of sockeye salmon nursery lake productive capacity. Using data from 61 lakes across the NCC, we compared a suite of landscape and lake variables in an information theoretic framework producing a set of models relating these characteristics to lake PR. A categorical variable related to lake biogeochemistry—whether a lake is humic stained, clear, or glacially turbid—was the most important variable predicting lake PR and was included in all models. Lake surface area relative to upstream catchment size and lake perimeter‐to‐surface‐area ratio were also important, with smaller upstream catchments yielding higher production, and high shoreline complexity correlated with lower productivity as measured by limnetic PR. Model‐averaged predictions of PR from the four models with the lowest residual error were created for 96 lakes currently lacking limnological assessments. These landscape models represent a valuable starting point for evaluating lake‐specific carrying capacities for data‐poor sockeye salmon populations under Canada's Wild Salmon Policy.

Climate and local environment structure asynchrony and the stability of primary production in grasslands - Benjamin Gilbert; Andrew S. MacDougall; Taku Kadoya; Munemitsu Akasaka; Joseph R. Bennett; Eric M. Lind; Habacuc Flores‐Moreno; Jennifer Firn; Yann Hautier; Elizabeth T. Borer; Eric W. Seabloom; Peter B. Adler; et al. (Global Ecology and Biogeography, 2020)
Aim Climate variability threatens to destabilize production in many ecosystems. Asynchronous species dynamics may buffer against such variability when a decrease in performance by some species is offset by an increase in performance of others. However, high climatic variability can eliminate species through stochastic extinctions or cause similar stress responses among species that reduce buffering. Local conditions, such as soil nutrients, can also alter production stability directly or by influencing asynchrony. We test these hypotheses using a globally distributed sampling experiment. Location Grasslands in North America, Europe and Australia. Time period Annual surveys over 5 year intervals occurring between 2007 and 2014. Major taxa studied Herbaceous plants. Methods We sampled annually the per species cover and aboveground community biomass [net primary productivity (NPP)], plus soil chemical properties, in 29 grasslands. We tested how soil conditions, combined with variability in precipitation and temperature, affect species richness, asynchrony and temporal stability of primary productivity. We used bivariate relationships and structural equation modelling to examine proximate and ultimate relationships. Results Climate variability strongly predicted asynchrony, whereas NPP stability was more related to soil conditions. Species richness was structured by both climate variability and soils and, in turn, increased asynchrony. Variability in temperature and precipitation caused a unimodal asynchrony response, with asynchrony being lowest at low and high climate variability. Climate impacted stability indirectly, through its effect on asynchrony, with stability increasing at higher asynchrony owing to lower inter‐annual variability in NPP. Soil conditions had no detectable effect on asynchrony but increased stability by increasing the mean NPP, especially when soil organic matter was high. Main conclusions We found globally consistent evidence that climate modulates species asynchrony but that the direct effect on stability is low relative to local soil conditions. Nonetheless, our observed unimodal responses to variability in temperature and precipitation suggest asynchrony thresholds, beyond which there are detectable destabilizing impacts of climate on primary productivity.

Dominant native and non‐native graminoids differ in key leaf traits irrespective of nutrient availability - Arthur A. D. Broadbent; Jennifer Firn; James M. McGree; Elizabeth T. Borer; Yvonne M. Buckley; W. Stanley Harpole; Kimberly J. Komatsu; Andrew S. MacDougall; Kate H. Orwin; Nicholas J. Ostle; Eric W. Seabloom; Jonathan D. Bakker; et al. (Global Ecology and Biogeography, 2020)
Aim Nutrient enrichment is associated with plant invasions and biodiversity loss. Functional trait advantages may predict the ascendancy of invasive plants following nutrient enrichment but this is rarely tested. Here, we investigate (a) whether dominant native and non‐native plants differ in important morphological and physiological leaf traits, (b) how their traits respond to nutrient addition, and (c) whether responses are consistent across functional groups. Location Australia, Europe, North America and South Africa. Time period 2007–2014. Major taxa studied Graminoids and forbs. Methods We focused on two types of leaf traits connected to resource acquisition: morphological features relating to light‐foraging surfaces and investment in tissue (specific leaf area, SLA) and physiological features relating to internal leaf chemistry as the basis for producing and utilizing photosynthate. We measured these traits on 503 leaves from 151 dominant species across 27 grasslands on four continents. We used an identical nutrient addition treatment of nitrogen (N), phosphorus (P) and potassium (K) at all sites. Sites represented a broad range of grasslands that varied widely in climatic and edaphic conditions. Results We found evidence that non‐native graminoids invest in leaves with higher nutrient concentrations than native graminoids, particularly at sites where native and non‐native species both dominate. We found little evidence that native and non‐native forbs differed in the measured leaf traits. These results were consistent in natural soil fertility levels and nutrient‐enriched conditions, with dominant species responding similarly to nutrient addition regardless of whether they were native or non‐native. Main conclusions Our work identifies the inherent physiological trait advantages that can be used to predict non‐native graminoid establishment, potentially because of higher efficiency at taking up crucial nutrients into their leaves. Most importantly, these inherent advantages are already present at natural soil fertility levels and are maintained following nutrient enrichment.

Nutrient availability controls the impact of mammalian herbivores on soil carbon and nitrogen pools in grasslands - Judith Sitters; E. R. Jasper Wubs; Elisabeth S. Bakker; Thomas W. Crowther; Peter B. Adler; Sumanta Bagchi; Jonathan D. Bakker; Lori Biederman; Elizabeth T. Borer; Elsa E. Cleland; Nico Eisenhauer; Jennifer Firn; et al. (Global Change Biology, 2020)
Grasslands are subject to considerable alteration due to human activities globally, including widespread changes in populations and composition of large mammalian herbivores and elevated supply of nutrients. Grassland soils remain important reservoirs of carbon (C) and nitrogen (N). Herbivores may affect both C and N pools and these changes likely interact with increases in soil nutrient availability. Given the scale of grassland soil fluxes, such changes can have striking consequences for atmospheric C concentrations and the climate. Here, we use the Nutrient Network experiment to examine the responses of soil C and N pools to mammalian herbivore exclusion across 22 grasslands, under ambient and elevated nutrient availabilities (fertilized with NPK + micronutrients). We show that the impact of herbivore exclusion on soil C and N pools depends on fertilization. Under ambient nutrient conditions, we observed no effect of herbivore exclusion, but under elevated nutrient supply, pools are smaller upon herbivore exclusion. The highest mean soil C and N pools were found in grazed and fertilized plots. The decrease in soil C and N upon herbivore exclusion in combination with fertilization correlated with a decrease in aboveground plant biomass and microbial activity, indicating a reduced storage of organic matter and microbial residues as soil C and N. The response of soil C and N pools to herbivore exclusion was contingent on temperature – herbivores likely cause losses of C and N in colder sites and increases in warmer sites. Additionally, grasslands that contain mammalian herbivores have the potential to sequester more N under increased temperature variability and nutrient enrichment than ungrazed grasslands. Our study highlights the importance of conserving mammalian herbivore populations in grasslands worldwide. We need to incorporate local‐scale herbivory, and its interaction with nutrient enrichment and climate, within global‐scale models to better predict land–atmosphere interactions under future climate change.

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

Changing estuaries and impacts on juvenile salmon: A systematic review - Emma E. Hodgson; Samantha M. Wilson; Jonathan W. Moore (Global Change Biology, 2020)
Estuaries are productive ecosystems providing important habitat for a diversity of species, yet they also experience intense levels of anthropogenic development. To inform decision‐making, it is essential to understand the pathways of impacts of particular human activities, especially those that affect species such as salmon, which have high ecological, social‐cultural and economic values. Salmon systems provide an opportunity to build from the substantial body of research on responses to estuary developments and take stock of what is known. We conducted a systematic English‐language literature review on the responses of juvenile salmon to anthropogenic activities in estuaries and nearshore areas asking: what has been studied, where are the major knowledge gaps and how do stressors affect salmon? We found a substantial body of research ( n = 167 studies; 1,369 comparative tests) to help understand responses of juvenile salmon to 24 activities and their 14 stressors. Across studies, 82% of the research was conducted in the eastern Pacific (Oregon and Washington, USA and British Columbia, Canada) showing a limited geographical scope. Using a semiquantitative approach to summarize the literature, including a weight‐of‐evidence metric, we found a range of results from low to moderate–high confidence in the consequences of the stressors. For example, we found moderate–high confidence in the negative impacts of pollutants and sea lice and moderate confidence in negative impacts from connectivity loss and changes in flow. Our results suggest that overall, multiple anthropogenic activities cause negative impacts across ecological scales. However, our results also reveal knowledge gaps resulting from minimal research on particular species (e.g. sockeye salmon), regions (e.g. Atlantic) or stressors (e.g. entrainment) that would be expedient areas for future research. With estuaries acting as a nexus of biological and societal importance and hotspots of ongoing development, the insights gained here can contribute to informed decision‐making.

Belowground Biomass Response to Nutrient Enrichment Depends on Light Limitation Across Globally Distributed Grasslands - Elsa E. Cleland; Eric M. Lind; Nicole M. DeCrappeo; Elizabeth DeLorenze; Rachel Abbott Wilkins; Peter B. Adler; Jonathan D. Bakker; Cynthia S. Brown; Kendi F. Davies; Ellen Esch; Jennifer Firn; Scott Gressard; et al. (Ecosystems, 2019)

Spatial heterogeneity in species composition constrains plant community responses to herbivory and fertilisation - Dorothee Hodapp; Elizabeth T. Borer; W. Stanley Harpole; Eric M. Lind; Eric W. Seabloom; Peter B. Adler; Juan Alberti; Carlos A. Arnillas; Jonathan D. Bakker; Lori Biederman; Marc Cadotte; Elsa E. Cleland; et al. (Ecology Letters, 2018)
Environmental change can result in substantial shifts in community composition. The associated immigration and extinction events are likely constrained by the spatial distribution of species. Still, studies on environmental change typically quantify biotic responses at single spatial (time series within a single plot) or temporal (spatial beta diversity at single time points) scales, ignoring their potential interdependence. Here, we use data from a global network of grassland experiments to determine how turnover responses to two major forms of environmental change – fertilisation and herbivore loss – are affected by species pool size and spatial compositional heterogeneity. Fertilisation led to higher rates of local extinction, whereas turnover in herbivore exclusion plots was driven by species replacement. Overall, sites with more spatially heterogeneous composition showed significantly higher rates of annual turnover, independent of species pool size and treatment. Taking into account spatial biodiversity aspects will therefore improve our understanding of consequences of global and anthropogenic change on community dynamics.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

The effect of aerobic walking and lower body resistance exercise on serum COMP and hyaluronan, in both males and females - Harry M. Roberts; Jonathan P. Moore; Jeanette M. Thom (European Journal of Applied Physiology, 2018)

Floodgate Operations and Fish Communities in Tidal Creeks of the Lower Fraser River (British Columbia, Canada) - Rebecca E. Seifert; Jonathan W. Moore (Estuaries and Coasts, 2018)

Risk management to prioritise the eradication of new and emerging invasive non-native species - Olaf Booy; Aileen C. Mill; Helen E. Roy; Alice Hiley; Niall Moore; Pete Robertson; Simon Baker; Matt Brazier; Mathilde Bue; Richard Bullock; Steve Campbell; Dominic Eyre; et al. (Biological Invasions, 2017)

A prospective study of mitochondrial DNA copy number and the risk of prostate cancer - Amy Moore; Qing Lan; Jonathan N. Hofmann; Chin-San Liu; Wen-Ling Cheng; Ta-Tsung Lin; Sonja I. Berndt (Cancer Causes & Control, 2017)

Evaluation of the ROS Inhibiting Activity and Mitochondrial Targeting of Phenolic Compounds in Fibroblast Cells Model System and Enhancement of Efficiency by Natural Deep Eutectic Solvent (NADES) Formulation - Erwann Durand; Jérôme Lecomte; Rashmi Upasani; Béatrice Chabi; Christelle Bayrasy; Bruno Baréa; Elodie Jublanc; Martyn J. Clarke; David J. Moore; Jonathan Crowther; Chantal Wrutniak-Cabello; Pierre Villeneuve (Pharmaceutical Research, 2017)

Response diversity, nonnative species, and disassembly rules buffer freshwater ecosystem processes from anthropogenic change - Jonathan W. Moore; Julian D. Olden (Global Change Biology, 2017)
Integrating knowledge of environmental degradation, biodiversity change, and ecosystem processes across large spatial scales remains a key challenge to illuminating the resilience of earth's systems. There is now a growing realization that the manner in which communities will respond to anthropogenic impacts will ultimately control the ecosystem consequences. Here, we examine the response of freshwater fishes and their nutrient excretion – a key ecosystem process that can control aquatic productivity – to human land development across the contiguous United States. By linking a continental‐scale dataset of 533 fish species from 8100 stream locations with species functional traits, nutrient excretion, and land remote sensing, we present four key findings. First, we provide the first geographic footprint of nutrient excretion by freshwater fishes across the United States and reveal distinct local‐ and continental‐scale heterogeneity in community excretion rates. Second, fish species exhibited substantial response diversity in their sensitivity to land development; for native species, the more tolerant species were also the species contributing greater ecosystem function in terms of nutrient excretion. Third, by modeling increased land‐use change and resultant shifts in fish community composition, land development is estimated to decrease fish nutrient excretion in the majority (63%) of ecoregions. Fourth, the loss of nutrient excretion would be 28% greater if biodiversity loss was random or 84% greater if there were no nonnative species. Thus, ecosystem processes are sensitive to increased anthropogenic degradation but biotic communities provide multiple pathways for resistance and this resistance varies across space.

Comparative genomic, proteomic and exoproteomic analyses of three Pseudomonas strains reveals novel insights into the phosphorus scavenging capabilities of soil bacteria - Ian D. E. A. Lidbury; Andrew R. J. Murphy; David J. Scanlan; Gary D. Bending; Alexandra M. E. Jones; Jonathan D. Moore; Andrew Goodall; John P. Hammond; Elizabeth M. H. Wellington (Environmental Microbiology, 2016)
Summary Bacteria that inhabit the rhizosphere of agricultural crops can have a beneficial effect on crop growth. One such mechanism is the microbial‐driven solubilization and remineralization of complex forms of phosphorus (P). It is known that bacteria secrete various phosphatases in response to low P conditions. However, our understanding of their global proteomic response to P stress is limited. Here, exoproteomic analysis of Pseudomonas putida BIRD‐1 (BIRD‐1), Pseudomonas fluorescens SBW25 and Pseudomonas stutzeri DSM4166 was performed in unison with whole‐cell proteomic analysis of BIRD‐1 grown under phosphate (Pi) replete and Pi deplete conditions. Comparative exoproteomics revealed marked heterogeneity in the exoproteomes of each Pseudomonas strain in response to Pi depletion. In addition to well‐characterized members of the PHO regulon such as alkaline phosphatases, several proteins, previously not associated with the response to Pi depletion, were also identified. These included putative nucleases, phosphotriesterases, putative phosphonate transporters and outer membrane proteins. Moreover, in BIRD‐1, mutagenesis of the master regulator, phoBR , led us to confirm the addition of several novel PHO‐dependent proteins. Our data expands knowledge of the Pseudomonas PHO regulon, including species that are frequently used as bioinoculants, opening up the potential for more efficient and complete use of soil complexed P.

The effect of vigorous running and cycling on serum COMP, lubricin, and femoral cartilage thickness: a pilot study - Harry M. Roberts; Jonathan P. Moore; Claire L. Griffith-McGeever; Matthew B. Fortes; Jeanette M. Thom (European Journal of Applied Physiology, 2016)

When the Tides Don’t Turn: Floodgates and Hypoxic Zones in the Lower Fraser River, British Columbia, Canada - Jennifer Gordon; Michael Arbeider; David Scott; Samantha M. Wilson; Jonathan W. Moore (Estuaries and Coasts, 2015)

Emergent stability in a large, free‐flowing watershed - Jonathan W. Moore; Michael P. Beakes; Holly K. Nesbitt; Justin D. Yeakel; David A. Patterson; Lisa A. Thompson; Corey C. Phillis; Douglas C. Braun; Corinna Favaro; David Scott; Charmaine Carr-Harris; William I. Atlas (Ecology, 2015)
While it is widely recognized that financial stock portfolios can be stabilized through diverse investments, it is also possible that certain habitats can function as natural portfolios that stabilize ecosystem processes. Here we propose and examine the hypothesis that free‐flowing river networks act as such portfolios and confer stability through their integration of upstream geological, hydrological, and biological diversity. We compiled a spatially (142 sites) and temporally (1980–present) extensive data set on fisheries, water flows, and temperatures, from sites within one of the largest watersheds in the world that remains without dams on its mainstem, the Fraser River, British Columbia, Canada. We found that larger catchments had more stable fisheries catches, water flows, and water temperatures than smaller catchments. These data provide evidence that free‐flowing river networks function as hierarchically nested portfolios with stability as an emergent property. Thus, free‐flowing river networks can represent a natural system for buffering variation and extreme events.

Anthropogenic‐based regional‐scale factors most consistently explain plot‐level exotic diversity in grasslands - Andrew S. MacDougall; Joseph R. Bennett; Jennifer Firn; Eric W. Seabloom; Elizabeth T. Borer; Eric M. Lind; John L. Orrock; W. Stanley Harpole; Yann Hautier; Peter B. Adler; Elsa Cleland; Kendi Davies; et al. (Global Ecology and Biogeography, 2014)
Aim Evidence linking the accumulation of exotic species to the suppression of native diversity is equivocal, often relying on data from studies that have used different methods. Plot‐level studies often attribute inverse relationships between native and exotic diversity to competition, but regional abiotic filters, including anthropogenic influences, can produce similar patterns. We seek to test these alternatives using identical scale‐dependent sampling protocols in multiple grasslands on two continents. Location Thirty‐two grassland sites in N orth A merica and A ustralia. Methods We use multiscale observational data, collected identically in grain and extent at each site, to test the association of local and regional factors with the plot‐level richness and abundance of native and exotic plants. Sites captured environmental and anthropogenic gradients including land‐use intensity, human population density, light and soil resources, climate and elevation. Site selection occurred independently of exotic diversity, meaning that the numbers of exotic species varied randomly thereby reducing potential biases if only highly invaded sites were chosen. Results Regional factors associated directly or indirectly with human activity had the strongest associations with plot‐level diversity. These regional drivers had divergent effects: urban‐based economic activity was associated with high exotic : native diversity ratios; climate‐ and landscape‐based indicators of lower human population density were associated with low exotic : native ratios. Negative correlations between plot‐level native and exotic diversity, a potential signature of competitive interactions, were not prevalent; this result did not change along gradients of productivity or heterogeneity. Main conclusion We show that plot‐level diversity of native and exotic plants are more consistently associated with regional‐scale factors relating to urbanization and climate suitability than measures indicative of competition. These findings clarify the long‐standing difficulty in resolving drivers of exotic diversity using single‐factor mechanisms, suggesting that multiple interacting anthropogenic‐based processes best explain the accumulation of exotic diversity in modern landscapes.

The ecological and evolutionary implications of microrefugia - Jonathan A. Mee; Jean‐Sébastien Moore (Journal of Biogeography, 2014)
Pleistocene microrefugia (or cryptic refugia) may be distinguished from macrorefugia (or conventional refugia) on the basis of two characteristics. First, microrefugia were smaller than macrorefugia and consequently supported smaller refugial populations. Second, microrefugia harboured less diverse biotic communities than macrorefugia. We propose that these characteristics have important implications for the ecology and evolution of species and populations that have a history of isolation in microrefugia. We propose four hypotheses regarding the evolution of microrefugial populations: (1) small effective population sizes associated with survival in microrefugia lead to reduced genetic diversity and influence the evolution of mating systems; (2) differences in environmental conditions between macro‐ and microrefugia lead to local adaptation; (3) reduced diversity increases ecological opportunity and promotes ecological divergence in microrefugia; and (4) reduced species diversity in microrefugia allows more specific species interactions and promotes coevolution among species. We urge biogeographers to study the evolutionary implications of isolation in microrefugia.

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Three nights of sleep deprivation does not alter thermal strain during exercise in the heat - Jonathan P. Moore; Adam D. Harper Smith; Umberto Di Felice; Neil P. Walsh (European Journal of Applied Physiology, 2013)

Tissue turnover and stable isotope clocks to quantify resource shifts in anadromous rainbow trout - Walter N. Heady; Jonathan W. Moore (Oecologia, 2013)

Stream community and ecosystem responses to the boom and bust of an invading snail - Jonathan W. Moore; David B. Herbst; Walter N. Heady; Stephanie M. Carlson (Biological Invasions, 2012)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

Nestedness patterns and the dual nature of community reassembly in C alifornia streams: a multivariate permutation‐based approach - Mark Novak; Jonathan W. Moore; Robert A. Leidy (Global Change Biology, 2011)
Many factors contribute to the nonrandom processes of extinctions and invasions that are changing the structure of ecological communities worldwide. These factors include the attributes of the species, their abiotic environment, and the interactions and feedbacks between them. The relative importance of these factors has been difficult to quantify. We used nested subset theory and a novel permutation‐based extension of gradient analysis to disentangle the direct and indirect pathways by which these factors affect the metacommunity structure of freshwater fishes inhabiting the streams tributary to the S an F rancisco B ay. Our analyses provide quantitative measures of how species and stream attributes may influence extinction vulnerability and invasion risk, highlight the need for considering the multiple interacting drivers of community change concurrently, and indicate that the ongoing disassembly and assembly of B ay A rea freshwater fish communities are not fully symmetric processes. Fish communities are being taken apart and put back together in only partially analogous trajectories of extinction and invasion for which no single explanatory hypothesis is sufficient. Our study thereby contributes to the forecasting of continued community change and its effects on the functioning of freshwater ecosystems.

Distribution and chromatic adaptation of phytoplankton within a shelf sea thermocline - Anna E. Hickman; Patrick M. Holligan; C. Mark Moore; Jonathan Sharples; Vladimir Krivtsov; Matthew R. Palmer (Limnology and Oceanography, 2009)
Observations of vertical gradients in phytoplankton community structure were made through the water column of the seasonally stratified Celtic Sea, including within the thermocline. A deep chlorophyll maximum (DCM) was located within the thermocline at all stations, coupled to the nitracline. Vertical gradients in phytoplankton community composition were routinely observed within the thermocline. The cell abundance maxima for Synechococcus occurred in the upper part of the DCM coincident with a picoeukaryote abundance minima. Picoeukaryote abundance typically increased at or just above the peak of the DCM. Diatoms were observed occasionally at the DCM peak. Pigment compositions and phytoplankton absorption spectra indicated that the different phytoplankton communities were chromatically well adapted to the spectral composition of irradiance at the depths where they occurred in the water column. Profiles of vertical eddy diffusivity revealed that timescales formixing between the phytoplankton layers within the thermocline were in excess of typical phytoplankton growth rates. The observed vertical gradients in community structure could therefore result from selection and niche partitioning of phytoplankton types on the light and nutrient gradient within the thermocline. The data further indicate that the pigments, light absorption characteristics, and cell size contribute to the phytoplankton selection process.

Improving Bayesian isotope mixing models: a response to Jackson et al. (2009) - Brice X. Semmens; Jonathan W. Moore; Eric J. Ward (Ecology Letters, 2009)
We recently described a Bayesian framework for stable isotope mixing models and provided a software tool, MixSIR, for conducting such analyses ( Ecol . Lett ., 2008; 11 :470). Jackson et al . ( Ecol. Lett. , 2009; 12:E1) criticized the performance of our software based on tests using simulated data. However, their simulation data were flawed, rendering claims of erroneous behaviour inaccurate. A re‐evaluation of the MixSIR source code did, however, uncover two minor coding errors, which we have fixed. When data are correctly simulated according to eqns (1)–(4) in Jackson et al. (2009) , MixSIR consistently and accurately estimated the proportional contribution of prey to a predator diet, and was surprisingly robust to additional unquantified error. Jackson et al. (2009) also suggested we use a Dirichlet prior on the source proportion parameters, which we agree with. Finally, Jackson et al. (2009) propose adding additional error parameters to our mixing model framework. We caution that such increases in model complexity should be evaluated based on data support.

Local and large‐scale climate forcing of Puget Sound oceanographic properties on seasonal to interdecadal timescales - Stephanie K. Moore; Nathan J. Mantua; Jonathan P. Kellogg; Jan A. Newton (Limnology and Oceanography, 2008)
The influence of climate on Puget Sound oceanographic properties is investigated on seasonal to interannual timescales using continuous profile data at 16 stations from 1993 to 2002 and records of sea surface temperature (SST) and sea surface salinity (SSS) from 1951 to 2002. Principal components analyses of profile data identify indices representing 42%, 58%, and 56% of the total variability at depth‐station combinations for temperature, salinity, and density, respectively, and 22% for water column stratification. Variability in the leading pattern of Puget Sound water temperature and salinity profiles is well correlated with local surface air temperatures and freshwater inflows to Puget Sound from major river basins, respectively. SST and SSS anomalies are informative proxies for the leading patterns of variations in Puget Sound temperature and salinity profiles. Using this longer time history of observations, we find that SST and SSS anomalies also have significant correlations with Aleutian Low, El Niñntilde;o‐Southern Oscillation, and Pacific Decadal Oscillation variations in winter that can persist for up to three seasons or reemerge the following year. However, correlations with large‐scale climate variations are weaker compared to those with local environmental forcing parameters.

Restoring plant species diversity and community composition in a ponderosa pine-bunchgrass ecosystem - Daniel C. Laughlin; Jonathan D. Bakker; Mark L. Daniels; Margaret M. Moore; Cheryl A. Casey; Judith D. Springer (Plant Ecology, 2008)

Incorporating uncertainty and prior information into stable isotope mixing models - Jonathan W. Moore; Brice X. Semmens (Ecology Letters, 2008)
Stable isotopes are a powerful tool for ecologists, often used to assess contributions of different sources to a mixture (e.g. prey to a consumer). Mixing models use stable isotope data to estimate the contribution of sources to a mixture. Uncertainty associated with mixing models is often substantial, but has not yet been fully incorporated in models. We developed a Bayesian‐mixing model that estimates probability distributions of source contributions to a mixture while explicitly accounting for uncertainty associated with multiple sources, fractionation and isotope signatures. This model also allows for optional incorporation of informative prior information in analyses. We demonstrate our model using a predator–prey case study. Accounting for uncertainty in mixing model inputs can change the variability, magnitude and rank order of estimates of prey (source) contributions to the predator (mixture). Isotope mixing models need to fully account for uncertainty in order to accurately estimate source contributions.

Spring‐neap modulation of internal tide mixing and vertical nitrate fluxes at a shelf edge in summer - Jonathan Sharples; Jacqueline F. Tweddle; J. A. Mattias Green; Matthew R. Palmer; Young-Nam Kim; Anna E. Hickman; Patrick M. Holligan; C. Mark Moore; Tom P. Rippeth; John H. Simpson; Vladimir Krivtsov (Limnology and Oceanography, 2007)
Measurements of the intra‐tidal and spring‐neap variation in the vertical flux of nitrate into the base of the sub‐surface chlorophyll maximum (SCM) were made at the shelf edge of the Celtic Sea, a region with strong internal mixing driven by an internal tide. The neap tide daily mean nitrate flux was 1.3 (0.9‐1.8, 95% confidence interval) mmol m ‐2 d ‐1 . The spring tide flux was initially estimated as 3.5 (2.3‐5.2, 95% confidence interval) mmol m ‐2 d ‐1 . The higher spring tide nitrate flux was the result of turbulent dissipation occurring within the base of the SCM as compared to deeper dissipation during neap tides and was dominated by short events associated with the passage of internal solitons. Taking into account the likely under‐sampling of these short mixing events raised the spring tide nitrate flux estimate to about 9 mmol m ‐2 d ‐1 . The neap tide nitrate flux was sufficient to support substantial new production and a considerable fraction of the observed rates of carbon fixation. Spring tide fluxes were potentially in excess of the capacity of the phytoplankton community to uptake nitrate. This potential excess nitrate flux during spring tides may be utilized to support new production during the lower mixing associated with the transition toward neap tide. The shelf edge is shown to be a region with a significantly different phytoplankton community as compared to the adjacent Celtic Sea and northeast Atlantic Ocean, highlighting the role of gradients in physical processes leading to gradients in ecosystem structure.

Spatial variability of stable isotopes and fossil pigments in surface sediments of Alaskan coastal lakes: Constraints on quantitative estimates of past salmon abundance - Curtis S. Brock; Peter R. Leavitt; Daniel E. Schindler; Susan P. Johnson; Jonathan W. Moore (Limnology and Oceanography, 2006)
We quantified spatial patterns of stable isotopes of N and C (δ 15 N, δ 13 C) and fossil pigment concentrations in the uppermost 10 mm of sediment (,10 yr) from 74 profundal locations and three spawning‐stream discharge areas in Lake Nerka, southwest Alaska. Sediment δ 15 N (4.3% ± 0.7%) and δ 13 C (−26.3% ± 1.2%) varied directly (δ 15 N) or inversely (δ 13 C) with water column depth, whereas concentrations of most fossil pigments from algae were negatively correlated with depth. Sediment δ 15 N and δ 13 C were poorly correlated with either fossil pigment abundance or the local densities of spawning salmon. Instead, coastal nursery lakes appeared to integrate marine‐derived nutrients rapidly into lakewide nutrient pools, suggesting that while individual cores may be used to reconstruct whole‐lake salmon densities, habitat‐specific variations of past fish populations cannot be quantified reliably from sedimentary analyses.

Disturbance of freshwater habitats by anadromous salmon in Alaska - Jonathan W. Moore; Daniel E. Schindler; Mark D. Scheuerell (Oecologia, 2004)

A KIDNEY EPITHELIAL CELL LINE FROM A BOLIVIAN SQUIRREL MONKEY - JONATHAN G. SCAMMELL; J. ALLAN TUCKER; JUDY A. KING; CHARLEEN M. MOORE; JAMES L. WRIGHT; CATHY M. TUCK-MULLER (In Vitro Cellular & Developmental Biology - Animal, 2002)

Phytoplankton distribution and survival in the thermocline - Jonathan Sharples; Mark C. Moore; Tom P. Rippeth; Patrick M. Holligan; David J. Hydes; Neil R. Fisher; John H. Simpson (Limnology and Oceanography, 2001)
Observations of the vertical structure of density, concentrations of chlorophyll a and nitrate, and turbulent dissipation rates were made over a period of 25 h in a well‐stratified shelf region in the Western English Channel, between neap and spring tides. Maximum turbulent dissipation at the base of the thermocline occurred almost 5 h after maximum tidal currents. This turbulence aids phytoplankton growth by supplying bottom‐layer nutrients into the subsurface chlorophyll maximum but reduces phytoplankton concentrations in the thermocline by mixing cells from the base of the subsurface maximum into the bottom mixed layer. The turbulent dissipation observations were used to estimate an average nitrate flux into the thermocline of 2.0 (0.8‐3.2, 95% confidence interval) mmol m −2 d −1 , which is estimated to have been capable of supporting new phytoplankton growth at a rate of 160 (64–256) mg C m −2 d −1 . Turbulent entrainment of carbon from the base of the subsurface biomass maximum into the bottom mixed layer was observed to be 290 (120–480) mg C m −2 d −1 . This apparent excess export from the chlorophyll maximum is suggested to be a feature of the spring‐neap cycle, with export dominating as the tidal turbulence increases toward spring tides and erodes the base of the thermocline. The observed rate of carbon export into the bottom mixed layer could account for as much as 25% of the gross annual primary production in stratifying shelf seas. Such turbulent losses, combined with grazing losses and low light levels, suggest that phytoplankton need to be highly adapted to environmental conditions within the thermocline in order to survive.

Characterisation of oxidised 7Fe dicluster ferredoxins with NMR spectroscopy - Jonathan P. Hannan; Johanneke L. H. Busch; Jacques Breton; Richard James; Andrew J. Thomson; Geoffrey R. Moore; S. L. Davy (JBIC Journal of Biological Inorganic Chemistry, 2000)

Effect of nickel(II) substitution on the resonance Raman and NMR spectra of Alcaligenes xylosoxidans azurin II: implications for axial-ligand bonding interactions in cupredoxin active sites - Jonathan P. Hannan; Sharon L. Davy; Geoffrey R. Moore; Robert R. Eady; C. R. Andrew (JBIC Journal of Biological Inorganic Chemistry, 1998)